Thermal characteristics of combined compressor - ejector refrigeration/heat pump systems for HVAC&R - Gjerasimovski, Aleksandar; Sharevska, Maja; Gjerasimovska, Natasha; Sharevska, Monika; Filkoski, Risto (National Library of Serbia, 2024)
Thermal characteristics of combined compressor ? ejector refrigeration/heat pump systems applied in heating, ventilation, air conditioning and refrigeration (HVAC&R) of buildings are investigated. An original model for estimation of the thermal characteristics of the combined cycles is developed, to determine the influence of the evaporation, interstage, condensation, and generating temperature conditions on mechanical and thermal COP of the combined system, and to optimize the thermal parameters of the cycle. Results are presented for different temperature conditions, with R134a as a suitable refrigerant. A comparison between the thermal characteristics of the simple mechanical vapor compression cycle, the simple ejector thermocompression cycle, and the combined compressor ? ejector refrigeration/heat pump cycle is given. The benefits of implementation of combined compressor ? ejector refrigeration/heat pump cycles in HVAC&R systems are discussed. The temperature lift or temperature difference between condensing temperature and interstage temperature significantly influences the thermal (ejector) COP. If temperature lift is between 10 K and 20 K, high values of thermal COP can be achieved (0.5-1.0, for generating temperature equal to 80?C; 1.0-1.8, for generating temperature equal to 120?C). If temperature lift is between 30 K and 40 K, very low values of COPth can be obtained